Strike a pose: the semiotics of electoral images in Cyprus after state independence in 1960 until 2013 - Zantides, Evripides; Zapiti, Anna (My University, 2014)
Political advertising as a communication process aims in attracting the viewers’ attention towards what a candidate or a party has to say with the ‘intention of influencing their political attitudes, beliefs and/or behaviors’ (Kaid, 2004). In electoral photography the candidate does not only attempt to establish a program with the voters but also a ‘personal link’ with them, articulated through ‘a style of life of which he is at once the product, the example and the bait’, heroized through the iconography of his appearance in familiar social settings, gestures and other predetermined set ups (Barthes, 1993). As Capistran (2013) argued, the posed, constructed and photographic image of the candidate in the studio or another controlled environment indicates the power of control by the individual represented. Dumitrescu (2010) identified two communication roles that political posters play; the first is to provide “factual” information about the candidates whilst the second is to present “nonverbal” information through pictures of the candidate, signaling behavioral intent. Political posters can also significantly alter their motivational and persuasive power simply by using images that elicit emotions such as fear or enthusiasm (Brader, 2005). Different feelings and preferences can be elicited through the image of the candidate alone. The purpose of this study is three-fold: to examine which non-verbal attributes/connotative mechanisms are used by candidates in the construction of their political image; to investigate the linguistic meaning of headlines–isolated and in respect of the candidate’s image; and to explore the semiotic characteristics of the typography used in the main headlines. One hundred and forty seven (n=147) political posters were taken for analysis. These posters came from presidential and parliamentary elections from the 1960s until 2013 in Cyprus. All posters include an image of the candidate. The posters were drawn from the Press and Information Office (PIO) in Cyprus, the archives of different newspapers and magazines and from various advertising agencies that have dealt with these posters. The methodology of content analysis was used and the coding frame developed was based on previous published work. The data revealed that there are changes in the connotation procedures on the photographic messages of the political candidates as well as in the linguistic meaning and the typography of the headlines used. The study shows that political images, linguistic messages and typography of headlines vary over a period of time and suggest that there are associations of these changes with socio-historical landmarks and events.
Keywords: Political advertising; Non-verbal attributes